Exploring the cooling effect of urban parks based on the ECOSTRESS land surface temperature - Liu, Yihui; Xu, Xinliang; Wang, Fei; Qiao, Zhi; An, Hongmin; Han, Dongrui; Luo, Jie (Frontiers in Ecology and Evolution, 2022)
Understanding the cooling effect (CE) of urban parks is vital to mitigate the urban heat islands. Ecosystem Spaceborne Thermal Radiometer Experiment on Space Station (ECOSTRESS) land surface temperature data (LST) data were used to construct diurnal thermal variations to explore the CE of urban parks in the fifth ring regions of Beijing. Local climate zone (LCZ) classification andbuilding data were also used to distinguish different parks and evaluate the impacts of buildings on the CE respectively. The results shown that urban parks tended to heat up slower than other regions during the daytime, and water releasing energy dominated the mean LST of parks at night. Large parks meeting the minimum area (40,000 m2) of LCZ had better CE inside each park during the daytime. 334 large parks were divided into six types of LCZ. The strength of the CE decrease with the increases of distance, and seemed to exist at a distance of up to 150-200 m. Such impacts of parks were insignificant at night. In addition, Parks containing certain dense trees and water had better CE inside and out. The height and density of buildings had a relatively obvious impact on the CE of parks. This study can provide insight into the impacts of urban parks on the urban thermal environment and promote the CE of urban parks in future urban planning.